A comparison of growth, antioxidant levels and fatty acid metabolism in juvenile rainbow trout (Oncorhynchus mykiss) reared in two different stocking densities: low and high. Issue 5 (2nd November 2017) - Bayır, Mehtap; Bayır, Abdulkadir
Abstract: The effects of high stocking density (HSD) on molecular, enzymatic, and biometric parameters of juvenile rainbow trout ( Oncorhynchus mykiss ) were compared to those of a low-density control group. The expression of genes related to growth, oxidative stress, and polyunsaturated fatty acid (PUFA) metabolism as well as antioxidant enzyme activities in the liver and muscle, the fatty acid composition of the whole fish and its growth parameters were determined in a control (10 kg/m 3 ) and HSD group (39 kg/m 3 ). At the end of a 60-day experiment: (1) Body weight change (BWC) decreased from 471.7% (control group) to 245.0% (HSD group); (2) Specific growth rate was 7.9%/day in the control group and 5.6%/day in the HSD group; (3) The level of n -3 PUFA and docosahexaenoic acid, the ratio of n -3/ n -6 PUFA and mRNA expression of Δ-6 desaturase in the liver and muscle, sod1 in the liver as well as elongase in the muscle increased in fish reared at HSD; (4) the mRNA transcript level of other genes in both tissues was down-regulated by HSD, except that of sod1 and gpx1 in the muscle, which remained almost unchanged; and (5) HSD decreased antioxidant enzyme activities and the level of lipid peroxidation in both tissues.